Body Awareness dan Gaya Hidup Sehat Dewasa Muda - Zahra, Audya Shabina; Febriani, Zulfa (Fakultas Psikologi Universitas YARSI, 2025)
The prevalence of chronic diseases is currently shifting towards young people, so individuals need to adopt a good and sustainable healthy lifestyle for their future health and well-being. However, Indonesian people have low awareness regarding health. Body awareness of health can encourage someone to evaluate their lifestyle and prevent long-term health problems. This study aimed to determine the relationship between body awareness and the dimensions of a healthy lifestyle in young adults. The participants were 102 young adults (Mean age = 22 years) in Jabodetabek, selected using a convenience sampling technique. The instruments used were the Body Awareness Questionnaire (BAQ), which has a good reliability coefficient (Alpha = .842), and the Health-Promoting Lifestyle Profile II (HPLP II), which has sufficient reliability (Alpha = .585 - .893). The results showed a significant positive relationship between body awareness and each dimension of a healthy lifestyle (r = .350–.483), including health responsibility, nutrition, physical activity, stress management, interpersonal relations, and spiritual growth. This suggests that higher body awareness is associated with a healthier lifestyle among young adults. Thus, promotional or educational programs from psychologists or health practitioners to promote a healthy lifestyle for the young adult generation can be carried out by increasing their knowledge and skills regarding body awareness.